A‐scan ultrasonography and optic nerve sheath diameter evaluation in children with acute liver failure. (12th January 2020) - De Bernardo, Maddalena; Vitiello, Livio; Capone, Michela; Rosa, Nicola
Abstract: In this Letter to the Editor we would like to comment the article by Das and colleagues, concerning the optic nerve sheath diameter evaluation with ultrasonography in children with acute liver failure. In particular, this letter highlights several limitations in the use of B scan for such a purpose and suggests a more precise assessment with the standardized A scan technique.